Serum uric acid to high-density lipoprotein cholesterol ratio is associated with stroke in the elderly: a population-based study - Jiang, Qingsong; Zhan, Guoyong; Liu, Yi; Jiang, Cai; Wang, Kang; Zheng, Guofu; Liu, Weixian; Ma, Jiangchun; Wang, Ming; Tang, Zhuxiao (Frontiers in Neurology, 2025)
PurposeThe ratio of serum uric acid (UA) to high-density lipoprotein cholesterol (HDL-c), known as UHR, has been identified as a novel marker for oxidative stress and metabolic disorders. This study focused on exploring the association between UHR and stroke risk among older adults in the United States.MethodsThis cross-sectional study utilized data from individuals aged 60 years and older, collected through the 1999–2018 National Health and Nutrition Examination Survey (NHANES). Stroke assessment was based on participants’ self-reported history. The association between UHR and stroke risk was analyzed using logistic regression, restricted cubic splines (RCS), subgroup analysis, and receiver operating characteristic (ROC) curves.ResultsThis study included a total of 16,562 older adults, and the proportion of stroke cases increased with higher UHR levels. After adjusting for confounders, multivariable logistic regression analysis revealed that individuals in the highest UHR quartile had an odds ratio of 1.48 (1.23–1.80) for stroke risk compared to those in the lowest quartile. Subgroup analyses further demonstrated a stronger association in non-diabetic populations. RCS analysis suggested a linear relationship. Based on ROC results, UHR outperformed UA and HDL-c.ConclusionHigher UHR levels are strongly associated with an increased risk of stroke in older adults. Additional large-scale prospective studies are required.